Pengaruh Komunikasi Guru Sejarah terhadap Interaksi Pembelajaran Melalui Kelas Virtual di Madrasah Aliyah Negeri 1 Medan - Ahmad Gifari Alamsyah; Nursapia Harahap (Education & Learning, 2022)
This study discusses the effect of communication between teachers and students on learning interactions through virtual classes at Madrasah Aliyah Negeri 1 Medan. The background of this research is that the success of the teaching and learning process is determined by the teacher factor. The teacher's task is to convey subject matter to students through communication interactions in the teaching and learning process that he does. The success of the teacher in delivering the material really depends on the smooth interaction of communication between the teacher and his students. The lack of communication has an impact on the message conveyed by the teacher. To achieve teaching and learning interactions, it is necessary to have clear communication between teachers (communicators) and students (communicants). So that students can be successful in their learning tasks, as well as teachers can successfully teach and educate in accordance with the goals to be achieved. This study uses simple linear regression data analysis which aims to determine whether there is an influence between teacher and student communication on learning interactions through virtual classes. Data collection techniques with the method of documentation and questionnaires. The questionnaire method was used to determine the level of communication between teachers and students on learning interactions through virtual classes. Based on the results of this study, it is hoped that it can provide information and input for teachers and students that communication in education is very important and has a good effect on learning interactions through students' virtual classes.